Agile software development : evaluating the methods for your organization - Koch, Alan S. (Artech House computing library., 2005)
"This is the first impartial book that offers an expert objective analysis of Agile software development methods together with much-needed tools for evaluating their suitability for a given organization. It reviews the philosophical underpinnings and objectives of the Agile Manifesto and the 12 Agile principles, and discuses in concrete detail each practice of the six most widely recognized Agile methods. Managers find concise and unbiased insight into adoption implications, the possible benefits that may accrue, and the potential pitfalls of the practices."--Jacket